2022
DOI: 10.3390/ph15070782
|View full text |Cite|
|
Sign up to set email alerts
|

Omeprazole Prevents Colistin-Induced Nephrotoxicity in Rats: Emphasis on Oxidative Stress, Inflammation, Apoptosis and Colistin Accumulation in Kidneys

Abstract: The clinical value of colistin, a polymyxin antibiotic, is limited by its nephrotoxicity. Omeprazole is a commonly prescribed proton pump inhibitor. The current study aimed to evaluate the effects of the concomitant administration of omeprazole on colistin-induced nephrotoxicity in rats. Omeprazole significantly ameliorated colistin nephrotoxicity as evidenced by prevention in the rise in the serum level of creatinine, urea and cystactin C as well as urinary N-acetylglucosamine activity. This was confirmed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…In vitro studies showed synergistic interaction of polymyxin with a range of non-antibiotic drugs [31]. The use of omeprazole prevented polymyxin E-induced nephrotoxicity in a rat model and was used in some horses concurrently to PolyB [32]. Metamizol on the other hand is reported to cause acute kidney injury in a low number of human patients and might have also influenced renal function in horses concurrently treated with this antipyretic drug in the present study [33].…”
Section: Discussionmentioning
confidence: 51%
“…In vitro studies showed synergistic interaction of polymyxin with a range of non-antibiotic drugs [31]. The use of omeprazole prevented polymyxin E-induced nephrotoxicity in a rat model and was used in some horses concurrently to PolyB [32]. Metamizol on the other hand is reported to cause acute kidney injury in a low number of human patients and might have also influenced renal function in horses concurrently treated with this antipyretic drug in the present study [33].…”
Section: Discussionmentioning
confidence: 51%
“…In the present research, AFE, as well as the administration of omeprazole, also showed a significant decline in MDA but significantly increased CAT, GSH, and SOD levels in the serum and gastric homogenates versus the positive control group. The study reported important antioxidant effects of omeprazole along with its acid-suppression activities [23].…”
Section: Discussionmentioning
confidence: 99%
“…In the original publication [ 1 ], there was a mistake in Figure 2. There was an error in the sub-image of the first row, last column.…”
mentioning
confidence: 99%